2014
DOI: 10.11646/phytotaxa.178.4.1
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Prescottia (Orchidaceae: Orchidoideae, Cranichideae)

Abstract: This study of Prescottia is based on fieldwork, in situ observations and study of herbarium material. Fifteen species are recognised for Prescottia: P. carnosa, P. densiflora, P. ecuadorensis, P. glazioviana, P. lancifolia, P. leptostachya, P. lojana, P. montana, P. mucugensis, P. oligantha, P. ostenii, P. phleoides, P. plantaginifolia, P. spiranthophylla, and P. stachyodes. Seven lectotypifications, one neotypification, and six new synonymies are proposed. Prescottia spiranthophylla is re-established, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…and Koellensteinia florida (Rchb.f.) Garay, two endemic species of the Atlantic Forest, in addition to nine species restricted to Brazil that occur in the Atlantic (Azevedo et al 2014). Most species in the study area, until now that is, have been known to expressive populations of more than 50 individuals, but E. williamsii, H. schenckii and V. palmarum have been considered threatened due to low numbers of individuals and/or restricted distributions in the area, and thus require specific conservation actions (Barberena et al 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…and Koellensteinia florida (Rchb.f.) Garay, two endemic species of the Atlantic Forest, in addition to nine species restricted to Brazil that occur in the Atlantic (Azevedo et al 2014). Most species in the study area, until now that is, have been known to expressive populations of more than 50 individuals, but E. williamsii, H. schenckii and V. palmarum have been considered threatened due to low numbers of individuals and/or restricted distributions in the area, and thus require specific conservation actions (Barberena et al 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…The specimens collected were herborized following the standard techniques of floristic-taxonomic studies (Mori et al 1985) and subsequently deposited in JPB and UFP herbaria. The specimens were identified by consulting the specialized literature (Pabst & Dungs 1975, 1977Siegerist 1986;Chase 1986;Salazar et al 1990;Hágsater et al 1993;Carnevali & Romero 1996;Pupulin 2007;Romero-González et al 2008;Hágsater et al 2008;Hágsater et al 2010;Arenas & Cribb 2010;Peraza-Flores 2012;Romero-González et al 2013;Azevedo et al 2014;Carvalho et al 2016;Royer et al 2017;Bastos et al 2018;Pessoa & Alves 2016a,b, 2018 and by comparisons with photographs or digital images of type specimens accessed using the online databases Tropicos (http://www.tropicos. org/), JSTOR Global Plants (https://plants.jstor.org/), Virtual Herbarium Reflora (http://reflora.jbrj.gov.br) and speciesLink (https://specieslink.net/) .…”
Section: Methodsmentioning
confidence: 99%
“…Collected specimens were identified based on relevant literature related to the family, including nomenclatural and taxonomic revisions (e.g. Pinheiro and de Barros 2007, 2008, Romero-González et al 2008, Azevedo et al 2014, as well as comparisons with types and specimens already identified by orchid experts and deposited in herbaria. An identification key and a set of brief morphological descriptions are presented for all species based on herborized material complemented with field observations.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Prescottia plantaginifolia is morphologically variable and could be confused with P. spiranthophylla, a recently reestablished species (Azevedo et al 2014). Both species have green flowers, outer surface of lip with trichomes at the base and dorsal surface of column covered by trichomes, but P. plantaginifolia has lax inflorescences with non-overlapping flowers, whereas P. spiranthophylla has congested inflorescences with overlapping flowers (Azevedo et al 2014).…”
Section: Cyrtopodium Flavum and Cyrtopodium Glutiniferummentioning
confidence: 99%
See 1 more Smart Citation